2020
DOI: 10.3389/fnagi.2020.566391
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of P3 Event-Related Potential During Working Memory Across the Spectrum of Cognitive Aging

Abstract: Event-related potentials (ERPs) offer unparalleled temporal resolution in tracing distinct electrophysiological processes related to normal and pathological cognitive aging. The stability of ERPs in older individuals with a vast range of cognitive ability has not been established. In this test-retest reliability study, 39 older individuals (age 74.10 (5.4) years; 23 (59%) women; 15 non β-amyloid elevated, 16 β-amyloid elevated, 8 cognitively impaired) with scores on the Montreal Cognitive Assessment (MOCA) ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
(65 reference statements)
1
15
1
Order By: Relevance
“…These correlation coefficients are slightly higher than those found in our study (ranging between 0.55 and 0.68), which may be because our study focused on older adults with a wide range of cognitive ability. Previous studies have shown a potential confounding effect of cognitive impairment on the reliability of EEG ERP [ 9 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These correlation coefficients are slightly higher than those found in our study (ranging between 0.55 and 0.68), which may be because our study focused on older adults with a wide range of cognitive ability. Previous studies have shown a potential confounding effect of cognitive impairment on the reliability of EEG ERP [ 9 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive description of the 7-min test is provided elsewhere [ 9 ]. In short, each n -back test comprised 180 trials, including 60 (33.3%) target trials and 120 (66.7%) nontarget trials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations